2019
DOI: 10.1111/fcp.12466
|View full text |Cite
|
Sign up to set email alerts
|

Felbamate produces antidepressant‐like actions in the chronic unpredictable mild stress and chronic social defeat stress models of depression

Abstract: Felbamate is an anticonvulsant used in the treatment of epilepsy. In this study, we investigated the antidepressant‐like actions of felbamate in mice. The effects of felbamate were first assessed using the forced swimming test (FST) and tail suspension test (TST), and then investigated in the chronic unpredictable mild stress (CUMS) and chronic social defeat stress (CSDS) models of depression. The changes in the hippocampal brain‐derived neurotrophic factor (BDNF) signaling cascade after chronic stress and fel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…It is well known that long-term exposure to stress, as well as other conditions that contribute to the depressive-like behavior in animals, is accompanied by a BDNF expression decrease in the prefrontal cortex and in the hippocampus, while an increase in the level of neurotrophin has been observed in the nucleus accumbens [56,57]. In particular, numerous studies reported a decrease in the BDNF mRNA or protein levels, as well as an attenuation of TrkB receptor activity (detected by the level of phosphorylation of tyrosine residues at Tyr 706/707 ) and a decrease of Tyr 515 and Tyr 816 phosphorylation in the prefrontal cortex and hippocampus of rodents subjected to UCMS, that is consistent with the depression-like behavior [23,55,58]. In our study, a decrease of BDNF protein level both in the prefrontal cortex and the hippocampus in UCMS-induced depressed mice was found.…”
Section: Discussionmentioning
confidence: 59%
“…It is well known that long-term exposure to stress, as well as other conditions that contribute to the depressive-like behavior in animals, is accompanied by a BDNF expression decrease in the prefrontal cortex and in the hippocampus, while an increase in the level of neurotrophin has been observed in the nucleus accumbens [56,57]. In particular, numerous studies reported a decrease in the BDNF mRNA or protein levels, as well as an attenuation of TrkB receptor activity (detected by the level of phosphorylation of tyrosine residues at Tyr 706/707 ) and a decrease of Tyr 515 and Tyr 816 phosphorylation in the prefrontal cortex and hippocampus of rodents subjected to UCMS, that is consistent with the depression-like behavior [23,55,58]. In our study, a decrease of BDNF protein level both in the prefrontal cortex and the hippocampus in UCMS-induced depressed mice was found.…”
Section: Discussionmentioning
confidence: 59%
“…It is known that catecholamine synthesis is essential for providing an adequate response to any stressful situation, and there are many studies that investigate how they act in the face of different stressors, their route of action, and the different responses of the organism in the face of acute or chronic stress [ 18 , 19 , 20 , 21 , 22 , 23 ]. However, few of them focus on studying how the response to a stressor would be when the catecholamine synthesis is reduced.…”
Section: Discussionmentioning
confidence: 99%
“…To study the different responses that various stressors can have on the interactions that occur between the nervous, immune, and endocrine systems, different animal models have been proposed. Some of the most commonly employed stressors are restraint, social disruption, cold exposure, restraint with cold exposure, electric shock, forced swimming, food deprivation, wet sawdust, cage agitation, cat odor exposure, or reversal of the light/dark cycle [ 18 , 19 , 20 , 21 , 22 , 23 ]. Most of these methods report different effects that acute stress can have on animals, such that if they involve eustress for them, they will benefit the health of the animals, whereas if they involve distress, they could impair it.…”
Section: Introductionmentioning
confidence: 99%